Balanced Coagonist of GLP-1 and Glucagon Receptors Corrects Dyslipidemia by Improving FGF21 Sensitivity in Hamster Model - Patel, Vishal; Joharapurkar, Amit; Kshirsagar, Samadhan; Patel, Hiren M.; Pandey, Dheerendra; Patel, Dipam; Sutariya, Brijesh; Patel, Maulik; Bahekar, Rajesh; Jain, Mukul R. (Drug Research, 2017)
Hyperlipidemia is often associated with obesity and diabetes, and can lead to serious complications like atherosclerosis and fatty liver disease. Coagonist of GLP-1 and glucagon receptors is a therapy under clinical investigation for treatment of obesity and diabetes. In this study, we have characterized the mechanism of hypolipidemic effect of a balanced coagonist using high cholesterol-fed hamsters. Tyloxapol-induced hypertriglyceridemia, lipolysis in adipose tissue, and bile homeostasis were assessed after repeated dose treatment of the coagonist of GLP-1 and glucagon receptors (Aib2 C24 chimera 2, SC). Antagonists of GLP-1, glucagon, and FGF21 receptors were coadministered, and FGF21 sensitivity was determined in liver and adipose tissue. Repeated dose treatment of coagonist reduced cholesterol and increased FGF21 in blood and liver. Coagonist treatment reduced hepatic triglyceride secretion, increased lipolysis and reduced body weight. Antagonism of GLP-1 and glucagon receptors partially blocked the effect of the coagonist on lipid metabolism in circulation and liver, while FGF21 receptor antagonist completely abolished it. Glucagon and GLP-1 receptors antagonists blocked the action of coagonist on cholesterol excretion and bile flow in liver, but FGF21 antagonist was not effective. Treatment with the coagonist increased expression of FGF21, FGF21R and cofactor ßKlotho in liver and adipose. In conclusion, coagonist of GLP-1 and glucagon receptors improved lipid metabolism in liver of dyslipidemic hamsters. This effect is partially mediated by GLP-1 and glucagon receptors, and the improved FGF21 sensitivity could be the mechanism of hypolipidemic action of the coagonist of GLP-1/glucagon receptors.
Keywords: insulin/glucagons; lipid-lowering drugs; drug research